The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1542/peds.2007-1307
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Autoimmune Neuropsychiatric Disorders Associated With Streptococcus: Comparison of Diagnosis and Treatment in the Community and at a Specialty Clinic

Abstract: OBJECTIVES-This study aimed to examine whether pediatric autoimmune neuropsychiatric disorders associated with streptococcus were appropriately diagnosed in the community and to determine subsequent rates of unwarranted use of antibiotic treatment for tics and obsessivecompulsive symptoms without the identification of an infection. METHODS-The design was a retrospective, cross-sectional, observational study of 176 children and adolescents who were evaluated in a specialty program for tics, Tourette's disorder,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 33 publications
2
40
1
3
Order By: Relevance
“…A recent examination of youth classified as PANDAS by their community physicians found that 61% did not strictly meet the NIH criteria for PANDAS (Gabbay et al 2008). During the history gathering process, careful attention should be given to reports of repeated, frequent infections; evidence of GAS in a young child (e.g., unexplained abdominal pain accompanied by fever); scarlet fever; brief episodes of tics; OCD or compulsive urination, which remitted; and especially sudden onset of OCD or tics accompanying an infectious illness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent examination of youth classified as PANDAS by their community physicians found that 61% did not strictly meet the NIH criteria for PANDAS (Gabbay et al 2008). During the history gathering process, careful attention should be given to reports of repeated, frequent infections; evidence of GAS in a young child (e.g., unexplained abdominal pain accompanied by fever); scarlet fever; brief episodes of tics; OCD or compulsive urination, which remitted; and especially sudden onset of OCD or tics accompanying an infectious illness.…”
Section: Discussionmentioning
confidence: 99%
“…Many children presenting with a PANDAS-like presentation do not have this level of documentation to support GAS infection. Rigorous application of full diagnostic criteria for PANDAS is not always employed in the community setting, and the practice of unwarranted use of antibiotics in children without objective laboratory evidence of infection could increase antibiotic resistance in the pediatric population (Gabbay et al 2008). It is this lack of a definitive diagnosis of GAS infection that lends to ambiguity and skepticism in establishing GAS relatedness to OCD/tic onset.…”
Section: Serologic and Prospective Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…PANDAS could be a diagnosis that is not thought of acutely and GABHS are not routinely investigated or screened for in the community making unnecessary treatment with antibiotics more likely if a GABHS infection is presumed rather than confirmed. 12 The PANDAS diagnostic criteria also state that infection and the symptoms should be temporally related. 5 The temporal relationship between GABHS and symptom exacerbation can vary over the course of the illness and in cases of rheumatic fever there can be a delay of up to six to nine months between evidence of infection and the appearance of symptoms of Sydenham's chorea.…”
mentioning
confidence: 99%